Balanced Scorecard Untuk Mengukur Kinerja Koperasi Secara Komprehensif - Franklin K. Genta (Coopetition : Jurnal Ilmiah Manajemen, 2020)
This research aims to apply the Balanced Scorecard method to measure cooperative performance comprehensively (thoroughly). Balanced Scorecard is one of the simple methods based on data from cooperative financial statements and questionnaires so that cooperative management can find out cooperative performance accurately and comprehensively through four main perspectives in the Balanced Scorecard , namely financial perspective, customer perspective, internal business perspective, and learning perspective and growth. Thus, cooperatives can find out and measure their performance both financial performance (short-term performance) and non-financial performance (long-term performance).